Allelic differences in a vacuolar invertase affect Arabidopsis growth at early plant development - Coluccio Leskow, Carla; Dominguez, Pia Guadalupe; Díaz Zirpolo, José Antonio; Obata, Toshihiro; Kamenetzky, Laura; Costa, Hernán; Taboga, Oscar Alberto; Marti, Hector Ruben; Keurentjes, Joost; Sulpice, Ronan; Ishihara, Hirofumi; Stitt, Mark; et al. (2017)
Improving carbon fixation in order to enhance crop yield is a major goal in plant sciences. By quantitative trait locus (QTL) mapping, it has been demonstrated that a vacuolar invertase (vac-Inv) plays a key role in determining the radical length in Arabidopsis. In this model, variation in vac-Inv activity was detected in a near isogenic line (NIL) population derived from a cross between two divergent accessions: Landsberg erecta (Ler) and Cape Verde Island (CVI), with the CVI allele conferring both higher Inv activity and longer radicles. The aim of the current work is to understand the mechanism(s) underlying this QTL by analyzing structural and functional differences of vac-Inv from both accessions. Relative transcript abundance analyzed by quantitative real-time PCR (qRT-PCR) showed similar expression patterns in both accessions; however, DNA sequence analyses revealed several polymorphisms that lead to changes in the corresponding protein sequence. Moreover, activity assays revealed higher vac-Inv activity in genotypes carrying the CVI allele than in those carrying the Ler allele. Analyses of purified recombinant proteins showed a similar K m for both alleles and a slightly higher V max for that of Ler. Treatment of plant extracts with foaming to release possible interacting Inv inhibitory protein(s) led to a large increase in activity for the Ler allele, but no changes for genotypes carrying the CVI allele. qRT-PCR analyses of two vac-Inv inhibitors in seedlings from parental and NIL genotypes revealed different expression patterns. Taken together, these results demonstrate that the vac-Inv QTL affects root biomass accumulation and also carbon partitioning through a differential regulation of vac-Inv inhibitors at the mRNA level.